THE CONTRIBUTION OF GENDER DIFFERENCES ON THE VOCABULARY LEARNING STRATEGIES - Riandi, Riandi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2018)
(Title: The Contribution of Gender Differences on The Vocabulary Learning Strategies). The present research study describes the contribution of gender differences on the vocabulary learning strategies. The purposes of this research are to reveal whether male and female learners use the vocabulary learning strategies at the same rate as well as to compare the differences in vocabulary learning strategies used by both male and female learners. A questionnaire was used to obtain the data. The data obtained from the questionnaire were analysed quantitatively. There were 20 respondents participated in this research study. They were the students of MTs Negeri 6 Gunungkidul. The results show that there are generally insignificant differences in terms of vocabulary learning strategies used by male and female students. Female students are at the higher use of determination strategies and males are higher at social strategies.Keywords: vocabulary learning strategies, gender differences, L2 learners